Understanding Green Product Purchase Decisions Among Generation Z in Indonesia: An Analysis Using Structural Equation Modelling - Azhari, Sulaiman; Albana, Abduh Sayid; Zunaidi, Rizqa Amelia (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Indonesia faces significant environmental challenges, with plastic waste pollution remaining a major issue. To address this, businesses are increasingly offering green products, yet consumer adoption—especially among Generation Z—remains limited. This study aims to identify the key factors influencing green product purchase decisions among Generation Z in Indonesia. A quantitative approach was employed, collecting data from 500 Gen Z respondents who have experience using green products. Structural Equation Modeling (SEM) was used to analyze the relationships among variables, including green attitude, green value, green knowledge, price, performance, convenience, preference, perception, purchase decision, and utility. The results show that green value, green knowledge, and performance significantly influence preferences and perceptions, which in turn positively affect purchase decisions and perceived utility. However, green attitude, price, and convenience do not have a significant direct effect. These findings suggest that increasing green value, knowledge, and product performance can enhance green product adoption among Indonesian youth. The study provides practical insights for companies and policymakers to design more effective strategies targeting Generation Z consumers and contributes to the broader understanding of sustainable consumption behavior in emerging markets.